Aerodynamic Analysis of S809 Airfoil: A Stall Validation with RANS k-? Turbulence Models - Abobakr Al-Ttowi; Akmal Nizam Mohammed (International Journal of Integrated Engineering, 2025)
This study examines the aerodynamic efficacy of the S809 airfoil at six angles of attack: ?14.23°, ?5.15°, 0°, 5.13°, 9.22°, and 10.21°. It uses steady two-dimensional RANS with two closures: k–? SST (Menter) and k–? Standard. It also checks the results against wind-tunnel data from NREL. We digitized experimental pressure distributions with calibrated axes, which meant that there was a vertical error of ±0.03 in Cp was used, and the uncertainty in the integrated lift is about 10?³. Without re-processing, the reported experimental uncertainties from NREL were kept. The study links coefficient trends to the measured surface-pressure fields so that you don’t have to use integrals to see if they agree. Both models have a pre-stall range of 5.13° to 9.22°, and the curves and wake thickness match the measurements. The slope of the lift curve is also very close to what was found. There are differences between the start of the stall and the end of the load. The k–? SST model gets the order of the stalls right, but it makes them less intense. This means that the lift is a little too high and the pressure drag is a little too low at 9.22° and 10.21°. The k–? Standard model keeps separation from happening longer and gives the biggest lift overprediction and the lowest drag in the same range. When the incidence is negative, both models predict fewer losses than the tunnel data. The solutions show a small positive lift and drag matches well at about 0°. This means that the problem is with the residual circulation offset and not the friction model. The results show that design and control can work well between 5.13° and 9.22°. They also show where you need to calibrate or control the transition as the separation gets closer. A subsequent study will employ URANS to broaden the scope into the post-stall regime to rectify unsteady phenomena.